PROXIMATE CHEMICAL ANALYSIS OF IPOMOEA CARNEA AND ITS SODIUM HYDROXIDE PRETREATMENT TO OBTAIN FERMENTABLE SUGARS - A. SHARMA; R. K. BACHHETI; R. G. SHARMA (International Journal of Pharma and Bio Sciences, 2015)
Ipomoea carnea is rapid growing weed species found in many continents including America, Asia, Africa and Australia. Proximate chemical analysis was performed by TAPPI standard method reveals that Ipomoea carnea contains holocellulose (67.49%), pentosan (16.70%), lignin (18.08%) and ash (6.14%). A good amount of holocellulose in Ipomoea carnea can be converted into fermentable sugars for generation of biofuel. Bioconversion offers not only a cheap and safe method for disposal of such weeds, but it also has the potential to convert lignocellulosic wastes into usable forms such as fermentable sugars that could be finally used for ethanol production. Conversion of cellulose into sugars is done with the help of enzymatic hydrolysis. The yield of sugars can be improved by using different types of pretreatment of the substrate. These include physical pretreatments and chemical pretreatments. Sometimes combining two or more types of pretreatments increase the yield. In the present work, sodium hydroxide pretreatment was used for hydrolyzing the Ipomoea carnea into fermentable sugars. The chip form of Ipomoea Carnea were delignified with 1%, 3%, and 5% NaOH and then commercial cellulase enzyme pretreatment was used. Scanning Electron Microscopy analysis showed that significant changes occurred in the structure of Ipomoea carnea after pretreatment, which is favourable for the hydrolysis and saccharification. The maximum fermentable sugar (202.38) μgm/ μl was obtained with 3% NaOH at 500 C after 5 days of incubation.